Balmer Filaments in Tycho's Supernova Remnant: An Interplay between Cosmic-ray and Broad-neutral Precursors - Knezevic S; Lasker R; van de Ven G; Font J; Raymond JC; Bailer-Jones CAL; Beckman J; Morlino G; Ghavamian P; Hughes JP; Heng K (IOP PUBLISHING LTD, 2022)
We present H alpha spectroscopic observations and detailed modeling of the Balmer filaments in the supernova remnant (SNR) Tycho (SN 1572). We used GH alpha FaS (Galaxy H alpha Fabry-Perot Spectrometer) on the William Herschel Telescope with a 3'.4 x 3'.4 field of view, 0 ''.2 pixel scale, and sigma(instr) = 8.1 km s(-1) resolution at 1 '' seeing for similar to 10. hr, resulting in 82 spatial-spectral bins that resolve the narrow H alpha line in the entire SN 1572 northeastern rim. For the first time, we can therefore mitigate artificial line broadening from unresolved differential motion and probe H alpha emission parameters in varying shock and ambient medium conditions. Broad H alpha line remains unresolved within spectral coverage of 392 km s-1. We employed Bayesian inference to obtain reliable parameter confidence intervals and to quantify the evidence for models with multiple line components. The median H alpha narrow-line (NL) FWHM of all bins and models is W-NL = (54.8 +/- 1.8) km s(-1) at the 95% confidence level, varying within [35, 72] km s(-1) between bins and clearly broadened compared to the intrinsic (thermal) approximate to 20 km s(-1). Possible line splits are accounted for, significant in approximate to 18% of the filament, and presumably due to remaining projection effects. We also find widespread evidence for intermediate-line emission of a broad-neutral precursor, with a median W-IL =(180 +/- 14) km s(-1) (95% confidence). Finally, we present a measurement of the remnant's systemic velocity, V-LSR = -34 km s(-1), and map differential line-of-sight motions. Our results confirm the existence and interplay of shock precursors in Tycho's remnant. In particular, we show that suprathermal NL emission is near-universal in SN 1572, and that, in the absence of an alternative explanation, collisionless SNR shocks constitute a viable acceleration source for Galactic TeV cosmic-ray protons.